Participatory Inclusive Education Programs for Sustainable Community Development - Raveenthiran Vivekanantharasa; Vicente Pironti; Emil Mirzayev; Muhammad Rafi Thoriq (SocietalServe: Journal of Community Engagement and Services, 2026)
This community engagement program aims to strengthen community empowerment through inclusive education practices using a participatory approach for sustainable development. The program was conducted in multicultural community settings involving local educators, parents, youth groups, and community leaders. Although inclusive education has gained increasing global attention, many communities still face challenges related to unequal educational access, limited awareness of diversity, and insufficient participation in inclusive learning activities. The program utilized participatory educational workshops, collaborative learning sessions, community mentoring, and inclusive capacity-building activities over a three-month period. A total of 50 participants from different community groups participated in the program. Quantitative findings indicated improvements in participants’ understanding of inclusive education principles, intercultural communication skills, and community collaboration practices